The Function of Phrasemes in Online Newspapers on the Topic of Global Crisis - Miletić, Nikolina (Slavia Centralis, 2024)
Phrasemes are prevalent in everyday speech and various types of texts, where they serve functions such as enhancing clarity, supporting argumentation, facilitating manipulation, conveying emotional expression, enabling evaluation, contributing to text constitution, and other (cf. Skog-Södersved 2007: 270-274). This study delves into the utilization of phrasemes in Croatian and German online newspapers that focus on the global crisis stemming from the pandemic, war, and inflation. The following research questions will be addressed: Which phrasemes are most commonly used? What are the underlying intentions for their use? In which sections of the text do they manifest? Who is the primary user of these phrasemes? What interlingual differences characterize their use in Croatian and German? The primary objective of this study is to discern interlingual disparities and similarities in the utilization of phrasemes in online newspapers.
Keywords: phrasemes, online newspapers, function of phrasemes, discourse analysis, Croatian and German newspaper articles